2024
DOI: 10.1029/2023jd039439
|View full text |Cite
|
Sign up to set email alerts
|

Lightning NOx in the 29–30 May 2012 Deep Convective Clouds and Chemistry (DC3) Severe Storm and Its Downwind Chemical Consequences

Kenneth E. Pickering,
Yunyao Li,
Kristin A. Cummings
et al.

Abstract: A cloud‐resolved storm and chemistry simulation of a severe convective system in Oklahoma constrained by anvil aircraft observations of NOx was used to estimate the mean production of NOx per flash in this storm. An upward ice flux scheme was used to parameterize flash rates in the model. Model lightning was also constrained by observed lightning flash types and the altitude distribution of flash channel segments. The best estimate of mean NOx production by lightning in this storm was 80–110 mol per flash, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 124 publications
(253 reference statements)
1
2
0
Order By: Relevance
“…The analysis showed that the LMA observations were well represented by two schemes. The ICEFLUX scheme (Finney et al, 2014) most closely replicated the observed flash rate trends during the first 4 hr of convection, which is important for the LNO x simulation reported in the companion paper (Pickering et al, 2024). ICEFLUX also provided the best estimate of the total flashes over the entire simulation.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The analysis showed that the LMA observations were well represented by two schemes. The ICEFLUX scheme (Finney et al, 2014) most closely replicated the observed flash rate trends during the first 4 hr of convection, which is important for the LNO x simulation reported in the companion paper (Pickering et al, 2024). ICEFLUX also provided the best estimate of the total flashes over the entire simulation.…”
Section: Discussionsupporting
confidence: 59%
“…The initial 8-hr simulation ran from 18:00 UTC on 29 May to 02:00 UTC on 30 May using 480 processors on the NCAR Yellowstone supercomputer. The simulation did not extend past 02:00 UTC because we were interested in this time period for atmospheric chemistry analyses when lightning would be influencing the NO x mixing ratios sampled by the DC3 aircraft in the anvil outflow (Pickering et al, 2024). For subsequent simulations a restart file was used at 21:00 UTC to reduce computation time since the observed convection began just after 21:00 UTC.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation